ASSESSMENT AND TREATMENT OF SOCIAL AVOIDANCE. Issue 1 (1st April 2013) - Harper, Jill M.; Iwata, Brian A.; Camp, Erin M.
Abstract Problem behavior maintained by social‐negative reinforcement often is evoked by a specific type of social interaction—the presentation of task demands. This study involved assessment and treatment of a more general form of social avoidance in which the establishing operation (EO) for problem behavior consisted of social interaction per se. Four subjects exhibited high rates of problem behavior during the play or demand conditions of a functional analysis (FA). A subsequent FA in which problem behavior produced escape from social interaction confirmed social avoidance for all subjects. A series of interventions aimed at attenuating aversive characteristics of social interaction then was implemented with 3 of the subjects. These interventions included vicarious reinforcement, conditioning of social interaction as a reinforcer, stimulus fading, and differential reinforcement (DRA) plus extinction (EXT). DRA plus EXT was the only condition in which decreases in problem behavior and increases in social interactions were observed reliably.